Evaluation of photoassisted treatments for norfloxacin removal in water using mesoporous Fe2O3-TiO2 materials. (15th May 2019) - García-Muñoz, Patricia; Zussblatt, Niels P.; Pliego, Gema; Zazo, Juan A.; Fresno, Fernando; Chmelka, Bradley F.; Casas, Jose A.
Abstract: We report the synthesis of mesoporous TiO2 and mesoporous Fe2 O3 -TiO2 catalysts by using a structure-directing-surfactant method, their characterization and their employment as photocatalysts for norfloxacin degradation in aqueous solution. The main findings show that in the presence of both O2 and H2 O2, Fe-containing mesoporous titania (Fe2 O3 -TiO2 ), with iron percentages between 1 and 3 wt%, exhibited norfloxacin degradation rates more than 60% greater than otherwise identical mesoporous titania without iron. Furthermore, the activity of the mesoporous composite catalysts also exceeds that of titania when illuminated with 405 nm light-emitting diodes. Iron loading improved the photocatalytic activity for norfloxacin degradation with values of apparent reaction rate constants of 0.037 min −1 and 0.076 min −1 with 1 and 3 surface wt.% of iron, respectively. An optimum of activity was found with the 3 wt% Fe2 O3 -TiO2 catalyst. Under these conditions, 10 mg/L of norfloxacin is reacted essentially to completion and 90% of total organic carbon conversion was obtained within 120 min of reaction. This higher organic carbon conversion degree was reached due to the photo-oxidation of short-chain organic acids. The high activity of the as-synthesized mesoporous composites is attributed to the additional iron phase which led to the different reactions for H2 O2 decomposition, but also due to the improvement in light absorbance. Finally, the activity of the most active catalyst was found to be stable over multiple sequential runs, which was related to a negligible amount of iron leaching (<0.1%) from these materials. Graphical abstract: Image 1 Highlights: Mesoporous Fe2 O3 -TiO2 catalysts displayed higher photoactivity than mesoporous TiO2. Fe2 O3 -TiO2 with H2 O2 under irradiation leads to improved pollutant degradation. A 90% of TOC conversion was obtained within 120 min of reaction under 405 nm LED light. Mesoporous Fe2 O3 -TiO2 catalysts were stable showing negligible iron leaching. A synergistic effect of photo-Fenton and photocatalysis has been demonstrated.